Proceedings of the International Conference on Nano-electronics, Circuits & Communication Systems - Nath, Vijay (Professor of Electronics and Communication Engineering) (Springer, 2017)
This volume comprises select papers from the International Conference on Nano-electronics, Circuits & Communication Systems(NCCS). The conference focused on the frontier issues and their applications in business, academia, industry, and other allied areas. This international conference aimed to bring together scientists, researchers, engineers from academia and industry. The book covers technological developments and current trends in key areas such as VLSI design, IC manufacturing, and applications such as communications, ICT, and hybrid electronics. The contents of this volume will prove useful to researchers, professionals, and students alike.
Keywords: Nanoelectronics -- Congresses.; Wireless communication systems -- Congresses.; elektronické knihy; electronic books